1977
DOI: 10.1177/107118137702100516
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Rotary Wing Aviator Precision Performance during Extended Helicopter Flights

Abstract: To insure the most effective utilization of his aviation resources, the rotary wing flight commander requires information which describes how extended flight time affects the operational capability of his flight crews. In response to this requirement, the US Army Aeromedical Research Laboratory has conducted an investigation of the man-helicopter system performance during five days of extended flight. The current report describes the changes in pilot performance and aircraft stability on one of the maneuvers p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Kimball and Anderson (1975) demonstrated that newly graduated rotary wing aviators can fly helicopters about 12 h in each 24-h period for 5 consecutive days with 3.5 h of sleep per 24-h period. The data reported from that study (Behar, Kimball, & Anderson, 1976;Kimball & Anderson, 1975;Lees, Kimball, & Stone, 1977;Lees, Simmons, Stone, & Kimball, 1978;Lees, Stone, Jones, Kimball, & Anderson, 1979) indicate that a pilot's ability to control a helicopter did not degrade as quickly as might have been expected. However, pilot response to the judgThe authors gratefully acknowledge the six Army aviators who served as subject pilots, the contributions of Major Lawrence R. Whitehurst, M.D., who served as the medical monitor and collected the flight surgeon evaluation data, Dr. Heber D. Jones, who guided and assisted in the 20-h/day week-long data-collection sessions on the VSAARL computer, William R. Holt, who guided us in the preparation and analysis of much of the data, and the more than 20 other laboratory research and support personnel who worked with us as associate investigators to make the conduct of this multidisciplinary project possible.…”
mentioning
confidence: 90%
“…Kimball and Anderson (1975) demonstrated that newly graduated rotary wing aviators can fly helicopters about 12 h in each 24-h period for 5 consecutive days with 3.5 h of sleep per 24-h period. The data reported from that study (Behar, Kimball, & Anderson, 1976;Kimball & Anderson, 1975;Lees, Kimball, & Stone, 1977;Lees, Simmons, Stone, & Kimball, 1978;Lees, Stone, Jones, Kimball, & Anderson, 1979) indicate that a pilot's ability to control a helicopter did not degrade as quickly as might have been expected. However, pilot response to the judgThe authors gratefully acknowledge the six Army aviators who served as subject pilots, the contributions of Major Lawrence R. Whitehurst, M.D., who served as the medical monitor and collected the flight surgeon evaluation data, Dr. Heber D. Jones, who guided and assisted in the 20-h/day week-long data-collection sessions on the VSAARL computer, William R. Holt, who guided us in the preparation and analysis of much of the data, and the more than 20 other laboratory research and support personnel who worked with us as associate investigators to make the conduct of this multidisciplinary project possible.…”
mentioning
confidence: 90%
“…However, only a few of these reports have dealt with specific issues involving fatigue among combat aircrews (Borowsky & Wall, 1983;Brictson, 1990;Brictson, Burger, & K e~e d y , 1971;Brictson, Burger, & Wulfeck, 1973;Brictson, Ciavarelli, & Wulfeck, 1969;Brictson, Hagen, & Wulfeck, 1967;Brictson, McHugh, & Naitoh, 1980;Brictson & Young, 1980;Krueger, Armstrong, & Cisco, 1985;Lees, Kimball, & Stone, 1977;Lees, Simmons, Stone, & Kimball, 1978;Lees, Stone, Jones, Kimball, &Anderson, 1979;Storm, 1980). Still fewer have investigated naval aviators in their own environment (i.e., aboard an aircraft carrier) during combat or peacetime fleet exercises (Brictson, 1990;Brictson et al, 1967;Brictson et al, 1969;, Brictson & Young, 1980.…”
mentioning
confidence: 95%